Experimental Study on the Ratio of Similar Materials in Weak Surrounding Rock Based on Orthogonal Design - Pengfei Jiao; Xiao Zhang; Xinzhi Li; Bohong Liu; Haojie Zhang (Journal of Engineering)
In the aspect of stability analysis of tunneling engineering, geomechanical model test is an important research method. A similar material is the prerequisite for the success of geomechanical model test. In the field of major engineering applications, a variety of similar materials are prepared for different geological conditions of surrounding rock and applied in some major engineering. With the use of standard sand, fine sand, and silt clay as materials, similar materials for weak surrounding rock were developed. Based on the orthogonal design method, through the direct shear test, the range analysis and variance analysis of various factors affecting the physical and mechanical parameters of weak surrounding rock are carried out. The results show similar material can meet the requirements in weak surrounding rock. Standard sand is the key factor that influences the internal friction angle of similar materials, and silt clay is the key factor affecting the cohesion of similar materials. Similar materials can meet the elastic modulus and severe requirements of the weak surrounding rock and can be used for the weak surrounding rock engineering. The new type of similar material configuration is widely used in shallow buried tunnel entrance section and urban shallow buried excavation engineering, in addition to tunnel engineering in loess stratum, and the problems of engineering design and construction are solved through geomechanical model test.